TRANSFORMASI RUANG JALAN MENJADI RUANG SOSIAL – EKONOMI: STUDI KASUS AKTIVITAS KULINER MALAM DI GANG MAYONG, PURBALINGGA - Revi Aulia Purbandini; Eva Priyanti; Artanti Kusuma Ayu (Vastutara : Arsitektur, Digital, Sejarah, Struktur dan Lingkungan, 2025)
The transformation of streets into spaces for social and economic activities reveals how residents of small towns continuously negotiate their spatial and everyday lives. Gang Mayong in Purbalingga offers a vivid example: a vehicle corridor that appears ordinary by day transforms into a lively culinary street filled with interaction and sensory experiences at night. This transformation reflects a form of spatial adaptation born from the community’s creativity and collective effort to make the most of limited urban space. Through field observation, interviews, and morphological analysis, it becomes clear how simple elements—tents, folding tables, and modest lighting—blend with an oriental-style gate to create a distinctive hybrid visual identity. Amid the vibrant night economy, this space also serves as a social meeting ground that strengthens community ties. Yet, such dynamism brings new challenges, particularly regarding cleanliness and order. Therefore, adaptive and participatory design strategies are essential to ensure that this night culinary corridor continues to function not only as an arena for informal economic activity but also as a productive public space that preserves its oriental–vernacular character as an expression of local cultural identity.